Producción del cultivo de tabaco (Nicotiana tabacum L.) en época lluviosa y seca con diferentes tipos de fertilización. - Pilaguano Vega, Jonathan David (2024)
The present research project was carried out at La Playita Experimental Center which belongs to the Technical University of Cotopaxi, La Maná canton. The research was focused on evaluating tobacco crop production in two seasons, rainy and dry; with different types of fertilization. A completely randomized block design (CRBD) was employed with 4 treatments and 7 replications. The treatments were structured as follows: T1: Organic, T2: Inorganic, T3: Organic and Inorganic, and T4: Control. To determine differences between treatment means, statistical analysis was conducted by using the Tukey test at a 5% probability level. Morphological variables related to yields were considered, and a foliar chemical analysis was performed to determine pH and electrical conductivity parameters. The results of this research showed that the tobacco crop responded positively to the effect of mixed fertilization in the dry season, so achieving the best results with average values of 9.86 leaves/plant, 59.42 cm. and 35.62 cm. for leaf length and width, and leaf biomass of 723.99 g/plant, which are related to the achieved yields of 1671.7 (kg/ha). On the other hand, for the rainy season, lower results were evidenced compared to the dry season, but Treatment T2: Inorganic demonstrated acceptable results. The chemical parameters of leaf content were within average ranges with values of 5.28 for pH and 12.96 dS m-1 for EC. The economic analysis shows that Treatment 3 corresponding to the dry season presents a B/C ratio of 1.95, being very profitable relatively.